The Role of Body Fat in the Relationship of Cardiorespiratory Fitness with Cardiovascular Risk Factors in Brazilian Children - Garcia-Hermoso, A (Universidade Estadual Paulista - UNESP, 2018)
Aims: To analyze the association between the percentage of body fat and cardiorespiratory fitness (CRF) with cardiovascular risk factors in children, and; to examine whether percentage of body fat acts as a mediator on the association between CRF and cardiovascular risk factor. Methods: This cross-sectional study included 128 children aged 7-11 years (Mean 8.54, SD: 1.42). The following variables were evaluated: The percentage of body fat, CRF, diastolic and systolic blood pressure, glucose, triglycerides (TG) and total cholesterol. For statistical analysis were performed Partial correlation and mediation analysis. All analysis was adjusted for sex, age and height. Results: CRF, the percentage of body fat, mean arterial pressure (MAP) and TG showed a correlation between each other. Percentage of body fat mediated the association between CRF and MAP (Indirect Effect= -0.008; IC: -0.0159 -0.0030), explaining 29% of this association. However, it was found that the percentage of body fat was not a mediator of the association between CRF and TG. Conclusion: The percentage of body fat mediates the association between CRF and MAP. Our findings show that the importance of a healthy body composition for the prevention of high blood pressure levels in childhood as well as the relevance of physical activity on these parameters. © 2008 Verduci Editore s.r.l. All rights reserved.